Complementarity between informal care and formal care to adults: knowledge mapping through a scoping review of the literature - Matos, M.; Bobrowicz-Campos, E.; Silva, R.; Castanheira, F. (Complementarity between informal care and formal care to adults: knowledge mapping through a scoping review of the literature, 2023)
Background: Providing informal care to a relative is known to affect informal caregivers physical and mental health as well as their social relationships with other individuals and their community. The role and function of the informal caregiver can be complemented by community and/or health services, provided by formal caregivers, which might buffer the detrimental effects of providing informal care to informal caregivers’ health. Therefore, the aims of this scoping review are to map the (1) existing literature on different types of complementarities between formal and informal care and the (2) existing literature on the impact of this complementarity on informal caregivers’ health — physical, psychological, and social domains. Inclusion criteria: The review will consider qualitative, quantitative, and mixed-method studies that involved adult informal caregivers who care for their relatives suffering from chronic physical or neurological diseases, and that focused on the concept of complementarity of formal and informal care, describing or evaluating its potential to improve the physical, psychological, and social health outcomes of informal caregivers. There will be no restrictions with regard to geographical, sociocultural, or socioeconomic settings. Methods: The review will be conducted in accordance with the methodological principles for scoping review proposed by the JBI and in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR). The search for relevant published and unpublished studies will be carried out in the CINAHL Complete, MEDLINE via Ebsco, SciELO, Web of Science, Scopus, PsycINFO, APA PsychArticles, Psychology and Behavioural Science Collection, Open Dissertations, OpenGrey, RCAAP–Repositório Científico de Acesso Aberto de Portugal, and Catálogo de teses e Dissertações da CAPES. Articles written in English, Portuguese, Spanish, French and Polish will be considered for inclusion, with no time restriction regarding the period of their posting in the database. Two independent reviewers will screen retrieved documents and extract data using a tool developed for this review. Extracted data will be presented in tabular format and accompanied by narrative summary. Discussion: This review will allow to map the empirical evidence on the complementarity between informal and formal care, on informal caregivers. This study will provide insight on future community/health services’ design that are important resources for informal caregivers.